Back Cover: Carbon Dioxide Adsorption on CeO2(110): An XPS and NEXAFS Study (ChemPhysChem 14/2017). Issue 14 (30th June 2017) - Yang, Chengwu; Bebensee, Fabian; Chen, Jun; Yu, Xiaojuan; Nefedov, Alexei; Wöll, Christof
Abstract : The Back Cover picture illustrates how synchrotron‐based near‐edge X‐ray absorption fine structure (NEXAFS) spectroscopy and X‐ray photoelectron spectroscopy (XPS) are used to investigate carbon dioxide adsorption on ceria (110) surfaces. The investigations did not show any indication for CO2 reoxidizing reduced CeO2 . More information can be found in the Full Paper by Ch. Yang et al. onpage 1874 in Issue 14, 2017 (DOI:10.1002/cphc.201700240 ).